Conformal Lithium Peroxide Growth Kinetically Driven by MoS2/MoN Heterostructures Towards High‐Performance Li−O2 Batteries. Issue 9 (29th July 2022) - Gu, Yuting; Ma, Yong; Wei, Le; Lian, Yuebin; He, Ying; Su, Yanhui; Li, Xinjian; Peng, Yang; Deng, Zhao
Abstract: The morphological control and spatial accommodation of Li2 O2 discharge products on the oxygen cathode are crucial to bolstering both the Coulombic and round‐trip efficiencies of Li−O2 batteries. Herein, MoS2 /MoN heterostructures are constructed on carbon cloth to serve as the freestanding and binder‐free oxygen cathode for Li−O2 batteries, lending a low charge/discharge polarization of 0.79 V, a large specific capacity of 9.04 mAh cm −2, and a superb cycling stability beyond 800 h. Through comprehensive microscopic, electroanalytical and density function theory analyses, the superb electrochemical performance is attributed to the formation of a conformal and amorphous Li2 O2 layer, which is kinetically driven in virtue of the higher electric conductivity of MoN and stronger LiO2 intermediate adsorption on the heterostructures. This work advocates the merits of interfacial engineering to enhance the performance of Li−O2 batteries by manipulating the discharge product formation. Abstract : The growth of Li2 O2 layer : MoS2 /MoN heterostructures were fabricated by in‐situ partially conversion of MoS2 into MoN, unraveling that the high electrochemical performances in lithium‐O2 battery of MoS2 /MoN heterostructures compared with MoS2 and MoN were ascribed to their high electric conductivity and strong adsorption for LiO2 intermediate.